Experimentally validated general risk attitude among different ethnic groups in Vietnam - Huong Dien Pham; Sabine Liebenehm; Hermann Waibel (Leibniz Universität Hannover, Thailand Vietnam Socio Economic Panel (TVSEP), 2017)
In this paper, we compare experimentally measured individual risk attitudes and survey-based risk items for rural households in the province of Dak Lak in Southern Vietnam. In particular, we test whether the survey-based measure can be validated by a risk experiment among different ethnic groups. Albeit we find that ethnic minorities are on average more risk averse than the ethnic majority, our results show similar correlations between risk attitudes and socio-economic characteristics among the two ethnic groups. Testing the explanatory power of the survey-based risk item shows the validity of this measure among different ethnic groups. Our findings have potentially important implications. First, the survey-based item is effective to measure risk attitudes of a multiethnic community. Second, our findings also suggest that the assumption of a "self-reinforcing culture of poverty" which is often attributed to minority group of Vietnam should be challenged in the light of these results.
Keywords: C83; C93; Z19; 330; Ethnic minorities; Survey risk items; Risk experiments